Perancangan Aplikasi Keamanan Data Dengan Kombinasi Algoritma Kriptografi RC4 Dan One Time Pad - Anas, Irfan; Ginting, Guidio Leonarde; Ndruru, Eferoni; Sembiring, Abdul Sani; Zebua, Taronisokhi (STMIK Budi Darma, 2021)
Data is an important aspect that has important information in it, which includes numbers, characters, symbols, pictures, sounds, or other signs that can be used as information. Data are certain facts, thus producing information. Cryptography is often used to secure and encode text data, messages, or other information, so using cryptographic algorithms on text data is able to secure data that is very important to everyone. So the expected results from the RC4 Cryptography algorithm and One Time Pad, which are used in text data can help in securing or encoding very important text data, so that the text is not easy to read or know the original message.